Back to the Future: Using Organization Design Theory for Effective Organizational Networks. Issue 2 (7th February 2020) - Kenis, Patrick; Raab, Jörg
Abstract: In this article, we explore how classical organization theory can contribute to better comprehend the phenomenon "organizational networks." We will demonstrate that this juxtaposition can produce new and interesting insights. First, we argue that an organizational network can be understood as an organization following the classical definition by March and Simon. Second, we assume that organizational networks, as any other form of organizing, need to find solutions to four universal problems as suggested by Puranam and colleagues to be effective: task division, task allocation, reward provision, and information provision. Third, introducing and analyzing an existing organizational network for the management of housing expenses in a Dutch municipality helps us to reflect on how organizational networks in general and this network in particular have found solutions to the four problems of organizing. Finally, we present a number of interesting observations and implications resulting from the confrontation between organizational networks and organization theory and formulate a number of propositions to inspire and guide further research.